(untitled) (Global Journal of Human-Social Science, 2025)
This article explores the role of sacrificial rituals in ancient Greek religious practices, emphasizing their function as a means of establishing and maintaining communion between mortals and the divine. Sacrifices were integral to both individual and collective life, marking key transitions such as birth, initiation, warfare, and civic celebrations. Through an interdisciplinary approach combining literary, iconographic, and archaeological sources, this study examines the typologies of offerings, the material and symbolic significance of altars as the focal point of ritual activity, and the complex interplay between sacrificial practices and sociopolitical structures. Particular attention is given to the ideological and performative dimensions of blood sacrifices, as well as to the debated phenomenon of human sacrifice. By analyzing a broad spectrum of evidence, this article contributes to a nuanced understanding of how ritualized violence functioned as a mechanism of religious expression, social cohesion, and power negotiation in the ancient Greek world.